2020
DOI: 10.21082/jtidp.v7n3.2020.p163-178
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Biokimia dan Indikator Vigor Benih Kakao pada Lima Taraf Lamanya Penyimpanan

Abstract: <em>During the storage period, cocoa seeds undergo various processes that will affect the content of their food reserves and will have an impact on germination capacity and seeds vigor. The objective of this study is to investigate the changes of biochemical and vigor of cocoa seeds after storage for a maximum of 4 weeks with an interval of 1 week. The experiment was conducted at the Integrated Laboratory and Greenhouse of Balittri, Sukabumi, West Java, from October to December 2019. The completely rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
3
0
3
Order By: Relevance
“…In addition, according to Gifford [16], specific protein synthesis is needed to maintain embryonic dormancy. Also, the results of Sobari [17] study where cocoa seeds were stored for 4 weeks showed a higher protein content.…”
Section: Biochemical Response Of Seeds With the Use Of Silica Gelmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, according to Gifford [16], specific protein synthesis is needed to maintain embryonic dormancy. Also, the results of Sobari [17] study where cocoa seeds were stored for 4 weeks showed a higher protein content.…”
Section: Biochemical Response Of Seeds With the Use Of Silica Gelmentioning
confidence: 93%
“…Meanwhile, seed fat content tends to decrease by an average of 0.155%. Fat content decreased and fatty acid levels increased [17]. Decreased fat content in seeds due to the hydrolysis reaction of fat into fatty acids [18].…”
Section: Biochemical Response Of Seeds With the Use Of Silica Gelmentioning
confidence: 99%
“…In order to create fatty acid methyl ester, the free fatty acid has a significant impact on the transesterification of oils with an alcohol (methanol or ethanol) to produce fatty acid methyl (ethyl) esters using an alkaline catalyst. FFA reacts with the catalyst to generate soaps and impedes the separation of the product from the glycerol because viscosity or gels are formed, and the output and transesterification rates are reduced [20]. The increase in FFA due to the fat hydrolysis as a result of the storage process also occurred in studies of the storage of oats [15], pine [16], and soybeans [17] seeds.…”
Section: Effects Of Fruit Storage Duration On the Chemical Properties Of Kemiri Sunan Kernelmentioning
confidence: 99%
“…Kemungkinan tersebut sejalan dengan yang dinyatakan oleh Atdwiyani, Purwanti, & Muhartini (2017) bahwa pertumbuhan benih pada proses perkecambahan lanjut lebih dipengaruhi oleh ketersediaan unsur hara pada media tanam, sedangkan pada proses perkecambahan awal lebih dipengaruhi oleh cadangan makanan yang ada di dalam benih. Sejalan dengan hal itu, hasil penelitian Sobari et al (2020) pada benih kakao menunjukkan bahwa pada tahap awal perkecambahan, cadangan makanan berupa lemak diproses menjadi asam lemak, dan pada tahap selanjutnya asam lemak tersebut diperlukan dalam sintesa sukrosa yang akan menghasilkan energi yang dibutuhkan untuk mendukung pertumbuhan kecambah.…”
Section: Pengaruh Lama Perendamanunclassified